Upaya Meningkatkan Keterampilan Membaca dengan Metode Anak Hebat (AHE) - Fidiyaningrum , Anis; Handayani, Arri; Rakhmawati, Dini (PGRI Kota Semarang, 2024)
There are problems with students having difficulty reading almost every school year. For students in grade 1 elementary school, they are already faced with textbooks in the form of reading. When they were in kindergarten, they were not required to be able to read when they graduated. So the problem arises when grade 1 students are not fluent in reading, even though the subject matter is already in the form of reading. Therefore, the author makes an effort to improve reading skills in students by using the great child method (AHE). The AHE method consists of 6 steps, namely brain gymnastics, remediation, reading modules, enrichment, writing and games. With a maximum duration of about 30 minutes in each meeting, the students' concentration will be well maintained. The teacher provides guidance by giving praise, encouragement, and should not use negative words when students are wrong in reading. Hopefully, with teachers using the AHE method, there will be no more students who experience learning difficulties.